2004
DOI: 10.1111/j.0022-202x.2004.22401.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Tenascin-X Causes Abnormalities in Dermal Elastic Fiber Morphology

Abstract: Deficiency of the extracellular matrix protein tenascin-X (TNX) was recently described as the molecular basis of a new, recessive type of Ehlers-Danlos syndrome. Here we report gross abnormalities of the elastic fibers and microfibrils in the dermis of these patients, and reduced dermal collagen content, as determined by quantitative image analysis. The ascending, fine elastic fibers in the papillary dermis were absent or inconspicuous and had few branches. The coarse elastic fibers of the reticular dermis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 32 publications
5
74
0
Order By: Relevance
“…Mutations in COL3A1 result in vascular-type EDS. Recently, Zweers et al (22)(23)(24) suggested that a Tenascin-X mutation could well be a candidate for joint hypermobility. Those authors believe that complete or partial deficiency (haploinsufficiency) of Tenascin-X can result in 2 distinct hereditary CTDs in which hypermobility is present, indicating that Tenascin-X has an essential role in the mechanical properties of skin, ligaments, and tendons (23).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in COL3A1 result in vascular-type EDS. Recently, Zweers et al (22)(23)(24) suggested that a Tenascin-X mutation could well be a candidate for joint hypermobility. Those authors believe that complete or partial deficiency (haploinsufficiency) of Tenascin-X can result in 2 distinct hereditary CTDs in which hypermobility is present, indicating that Tenascin-X has an essential role in the mechanical properties of skin, ligaments, and tendons (23).…”
Section: Discussionmentioning
confidence: 99%
“…They were able to confirm normal appearing fibrils and reduced collagen content, but also noticed irregular and immature elastin fibers containing few or no microfibrils [36]. Elastin staining showed absence of fine elastic fibers in papillary dermis and fragmented or clumped elastic fibers in reticular dermis.…”
Section: Tenascin-x Elastogenesis and Matrix Remodelingmentioning
confidence: 93%
“…At the light microscopic level, it was apparent that the typical candelabra structures at the dermal-epidermal junction were disrupted, and the length of the fibers was dramatically reduced. Ultrastructure examination of the dermis showed abnormalities in both the microfibrillar and the elastin component in all tenascin-X-deficient patients with EDS (61). Whether the abnormalities arise during development by aberrant deposition of the elastic fibers or appear later in life by degradation of the elastic fiber is not known.…”
Section: Tenascin-x Deficiency and Elastic Fiber Abnormalitiesmentioning
confidence: 99%